INTERAKSI SOSIAL TOKOH HONAMI PENDERITA SINDROM OVARIUM POLIKISTIK DALAM NOVEL SEIBO - Fathiyyah Salsabila Az-Zahra Kamil; Mohammad Ali (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
This research is entitled Social Interaction of Honami Characters with Polycystic Ovary Syndrome in Novel Seibo which discusses polycystic ovary syndrome as the main setting that affects social interactions in the main character. The purpose of this study is to describe and analyze the form of social interaction of the Honami character in the novel Seibo. The research method used is a qualitative method using library research techniques and descriptive analysis with a sociology of literature approach. The results of this study are the social interactions contained in the novel Seibo include Associative which is a form of interaction in positive terms, and dissociative is a form of interaction in negative terms. Associative interactions in Honami include cooperation and accommodation. Meanwhile, dissociative interactions include conflict, competition, and contravention. Keywords : Seibo, Social Interaction, Associative, Dissociative